Psychometric properties of carer-reported outcome measures in palliative care: A systematic review - Michels, C; Boulton, M; Adams, A; Wee, B; Peters, M (SAGE Publications, 2015)
Background: Informal carers face many challenges in caring for patients with palliative care needs. Selecting suitable valid and reliable outcome measures to determine the impact of caring and carers’ outcomes is a common problem. Aim: To identify outcome measures used for informal carers looking after patients with palliative care needs, and to evaluate the measures’ psychometric properties. Design: A systematic review was conducted. The studies identified were evaluated by independent reviewers (C.T.J.M., M.B., M.P.). Data regarding study characteristics and psychometric properties of the measures were extracted and evaluated. Good psychometric properties indicate a high-quality measure. Data sources: The search was conducted, unrestricted to publication year, in the following electronic databases: Applied Social Sciences Index and Abstracts, Cumulative Index to Nursing and Allied Health Literature, The Cochrane Library, EMBASE, PubMed, PsycINFO, Social Sciences Citation Index and Sociological Abstracts. Results: Our systematic search revealed 4505 potential relevant studies, of which 112 studies met the inclusion criteria using 38 carer measures for informal carers of patients with palliative care needs. Psychometric properties were reported in only 46% (n = 52) of the studies, in relation to 24 measures. Where psychometric data were reported, the focus was mainly on internal consistency (n = 45, 87%), construct validity (n = 27, 52%) and/or reliability (n = 14, 27%). Of these, 24 measures, only four (17%) had been formally validated in informal carers in palliative care. Conclusion: A broad range of outcome measures have been used for informal carers of patients with palliative care needs. Little formal psychometric testing has been undertaken. Furthermore, development and refinement of measures in this field is required.